Analisis Karakteristik Bahan Tembaga Akibat Pengaruh Proses Penempaan Terhadap Kekuatan Impak - Siahaan, Muhammad Yusuf Rahmansyah; Siregar, Rakhmad Arief; Tanjung, Faisal Amri; Saktiawan, Agung (Fakultas Teknik UMSU, 2023)
Indonesia is one of the countries with the largest copper reserves in the world, namely the Tembagapura area, Mimika Regency, Papua Province. The development of electric car technology has a significant impact on increasing the demand for copper. This study conducted material engineering on copper materials with the forging process. The aim of the research was to obtain the average impact energy, average impact strength, and fracture shape of the material from a variety of copper materials. The variation of each test specimen was formed following the ASTM E23 standard with a size specification of 55 mmL x 10 mmW x 8 mmT. The experimental study of impact testing by the charpy method yielded an average impact energy value of 169.081 Joule and 98.058 Joule respectively for copper variations X1 and X2. The average impact strength values produced by the copper variations X1 and X2 are 2.114 J/mm2 and 1.226 J/mm2 respectively. The results of physical observations of the two variations of the copper material show that the material is not broken with fibrous fractures. The data from the test results can be declared that the forging process with hot working has an effect on increasing material characteristics by 58% and copper materials are classified as ductile materials.